2023
DOI: 10.1177/00219983231217131
|View full text |Cite
|
Sign up to set email alerts
|

Vibration behaviours of multi-debonded sandwich beams with symmetric angle-ply facesheets

Shang-Nan Tsai

Abstract: Sandwich beams, comprising two stiff facesheets bonded to a core, are light and strong and see widespread application. However, debonded regions between the facesheets and the core can significantly reduce the strength and have an impact on the vibration behaviour. In this study, the previous literature was referred to, and finite element simulations were conducted using ANSYS on debonded sandwich beams with [0°]4, [+45°/−45°]S and [90°]4 carbon fibre reinforced polymer facesheets. The effects of the configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Tsai researched the effect of different face sheet-core interface delamination configurations and face sheet arrangement orientations on the vibration behavior of composite sandwich beams. The findings revealed that maintaining distance between delaminations affected the vibration node position, an effect that resulted in larger reductions in the natural frequencies [19]. Kalgutkar and Banerjee investigated the free vibration of stiffened composite plates under hygrothermal conditions, emphasizing interfacial debonding at the plate-stiffener interface.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai researched the effect of different face sheet-core interface delamination configurations and face sheet arrangement orientations on the vibration behavior of composite sandwich beams. The findings revealed that maintaining distance between delaminations affected the vibration node position, an effect that resulted in larger reductions in the natural frequencies [19]. Kalgutkar and Banerjee investigated the free vibration of stiffened composite plates under hygrothermal conditions, emphasizing interfacial debonding at the plate-stiffener interface.…”
Section: Introductionmentioning
confidence: 99%